2019
DOI: 10.1063/1.5054091
|View full text |Cite
|
Sign up to set email alerts
|

Transition from electron accumulation to depletion at β-Ga2O3 surfaces: The role of hydrogen and the charge neutrality level

Abstract: The surface electronic properties of bulk-grown β-Ga2O3 (2¯01) single crystals are investigated. The band gap is found using optical transmission to be 4.68 eV. High-resolution x-ray photoemission coupled with hybrid density functional theory calculation of the valence band density of states provides insights into the surface band bending. Importantly, the standard linear extrapolation method for determining the surface valence band maximum (VBM) binding energy is found to underestimate the separation from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 78 publications
9
61
0
Order By: Relevance
“…While high n-type conductivity in β-Ga 2 O 3 can be efficiently achieved by impurity doping with Sn, Si, Ge, F or Cl [31,32] (and even metallic conductivity due to charge accumulation on the surface in undoped β-Ga 2 O 3 . [3,33] ), p-type conductivity is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…While high n-type conductivity in β-Ga 2 O 3 can be efficiently achieved by impurity doping with Sn, Si, Ge, F or Cl [31,32] (and even metallic conductivity due to charge accumulation on the surface in undoped β-Ga 2 O 3 . [3,33] ), p-type conductivity is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed hydrogen passivation of donors would be in contrast to theoretical predictions and to some experimental results obtained for H introduction at high temperatures during growth. [6][7][8] Note that the Fermi level in the H treated sample is pinned near E c -1.05 eV, suggesting this trap to be the main uncompensated deep center. This is opposite to that observed in DLTS on reference samples and 550 C annealed samples where the E2 Ã (E c -0.8 eV) trap is the major deep center.…”
mentioning
confidence: 98%
“…Hydrogen accumulation at the surface causes upwards band bending. 8 A question remains as to whether hydrogen behaves in Ga 2 O 3 as it often does in other semiconductors, i.e., forms neutral complexes with shallow donors or with deep level defects, thus passivating them. 11 One approach to check this is by introducing hydrogen (or deuterium) from plasmas.…”
mentioning
confidence: 99%
“…Recently, 2DEG has been found generally at the surfaces of oxide semiconductors, including CdO, [46] In 2 O 3 , [29a,d,47] SnO 2 , [29c,48] ZnO, [46b,49] IGZO, [29b] and possibly Ga 2 O 3 . [50] The 2DEG is confined at a few nanometers of near surface region, exhibiting properties such as increased electron mobility and reduced bandgap. Furthermore, 2DEG can also be created by modulating charge transfer at the interfaces of Mg x Zn 1-x O/ZnO, [51] LaAlO 3 /SrTiO 3 , [52] In 2 O 3 / ZnO, [53] and (Al x Ga 1-x ) 2 O 3 /Ga 2 O 3 .…”
Section: D Electron Gas (2deg) and 2d Hole Gas (2dhg) At Oxide Surfaces And Interfacesmentioning
confidence: 99%
“…[58] However, during the past decade, a series of studies performed on high-quality, low-defect single crystals or epitaxial thin films suggested the opposite situation where a surface electron accumulation layer (SEAL) confined within a few nm thick near the surface region with a concomitant downward band bending at the surfaces of CdO, [46a-e] In 2 O 3 , [29a,d,47] SnO 2 , [29c,48] ZnO, [46b,49] IGZO, [29b] and Ga 2 O 3 . [50] Furthermore, the downward band bending creates a confining potential well, leading to quantization of 2DEG. It should be mentioned that, although the SEAL is only a few nm thick, such layer can have a pronounced effect on the electronic properties of oxide films and the subsequent device performance.…”
Section: Surface 2degmentioning
confidence: 99%